2016
DOI: 10.1002/nau.22990
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Rho‐kinase and soluble guanylyl cyclase enzymes in prostate smooth muscle dysfunction in middle‐aged rats

Abstract: Prostate hypercontractility in middle-aging is associated with increased release of noradrenaline and Rho-kinase pathway, as well as with impairments of NO-sGC and β-adrenoceptor pathways. Middle-aged rats are suitable to explore the enhanced prostatic tone in the absence of prostate overgrowth. Neurourol. Urodynam. 36:589-596, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Few studies in the literature have addressed prostate smooth muscle contractility in 6 to 10-month-old rats. According to the published data, 10-month-old rats exhibited EFS-and phenylephrine-induced prostate smooth muscle hypercontractility (Calmasini et al, 2016), which are of the same magnitude as in the 8-month-old rats presented here. This is a valuable finding, suggesting that increased prostate smooth muscle contractility achieves a plateau in 8-month-old rats.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Few studies in the literature have addressed prostate smooth muscle contractility in 6 to 10-month-old rats. According to the published data, 10-month-old rats exhibited EFS-and phenylephrine-induced prostate smooth muscle hypercontractility (Calmasini et al, 2016), which are of the same magnitude as in the 8-month-old rats presented here. This is a valuable finding, suggesting that increased prostate smooth muscle contractility achieves a plateau in 8-month-old rats.…”
Section: Discussionsupporting
confidence: 83%
“…Besides the adrenergic pathway, it is well characterized that human and rodent prostates are also innerved by cholinergic and non-adrenergic noncholinergic neurons (Michel, Vrydag, 2006), which are altered during the aging process. For instance, 10-month-old rats exhibited increased prostate smooth muscle contractility to the purinergic agonist alpha, beta-methylene ATP and reduced isoproterenol (a betaadrenoceptor agonist)-induced prostate smooth muscle relaxation (Calmasini et al, 2016). In aged mice, increased PSM contraction induced by purinoceptor activation was associated with reduced ATP breakdown in the prostate (White et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The β-adrenoceptor activation counteracts the contractile pathways, contributes physiologically to maintain the prostatic tonus in several species and has been proposed as a new pharmacological therapeutic indication for BPH [37,38]. Studies in the literature have shown that impaired βadrenergic signaling plays a role in prostatic dysfunction in animal models of aging and hypertension [39,40]. However, to the best of our knowledge, no previous study evaluated this signaling pathway in prostatic tissue under obesity conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Protective effects of resveratrol on male urogenital tract dysfunction LUTS, ED, BPH and prostatitis are the most common UGT diseases. The main risk factors for these diseases include arterial hypertension, obesity, diabetes and ageing, which itself increases inflammation and oxidative status, thereby worsening the incidence and/or progression of UGT diseases (19)(20)(21) . Within this context, resveratrol has emerged as a potential candidate for the treatment of such diseases.…”
Section: Putative Mechanisms Of Action Of Resveratrolmentioning
confidence: 99%